Pemilihan kepala daerah yang demokratis Dalam perspektif UUD 1945 - Nopyandri ' (Fakultas Hukum Universitas Riau, 2011)
Direct election of regional heads have taken place since year 2005, that relied on by rule of UU of Number 32 Year 2004 with have base of rule section 18 article 4 Constitusional 1945. Inescapable fact in direct local elections in stages capitalization is emerging local elections that were far more expensive than the model of local elections by Parliament representatives as well as the nuances of the most notable is the rise of local election dispute is submitted to the Constitutional Court. Policy of the government and Parliament through Law No. 32 of 2004 which further amended by Act No. 12 of 2008 specifies that local elections are conducted in direct elections should be viewed as a political fact local election law.